Response of fibroblast growth factor 23 to volume interventions in arterial hypertension and diabetic nephropathy. Issue 46 (November 2016) - Humalda, Jelmer K.; Seiler-Mußler, Sarah; Kwakernaak, Arjan J.; Vervloet, Marc G.; Navis, Gerjan; Fliser, Danilo; Heine, Gunnar H.; de Borst, Martin H.
Abstract : Abstract: Fibroblast growth factor 23 (FGF-23) rises progressively in chronic kidney disease and is associated with adverse cardiovascular outcomes. FGF-23 putatively induces volume retention by upregulating the sodium-chloride cotransporter (NCC). We studied whether, conversely, interventions in volume status affect FGF-23 concentrations. We performed a post hoc analysis of 1) a prospective saline infusion study with 12 patients with arterial hypertension who received 2 L of isotonic saline over 4 hours, and 2) a randomized controlled trial with 45 diabetic nephropathy (DN) patients on background angiotensin-converting enzyme -inhibition (ACEi), who underwent 4 6-week treatment periods with add-on hydrochlorothiazide (HCT) or placebo, combined with regular sodium (RS) or low sodium (LS) diet in a cross-over design. Plasma C-terminal FGF-23 was measured by ELISA (Immutopics) after each treatment period in DN and before and after saline infusion in hypertensives. The patients with arterial hypertension were 45 ± 13 (mean ± SD) years old with an estimated glomerular filtration rate (eGFR) of 101 ± 18 mL/min/1.73 m 2 . Isotonic saline infusion did not affect FGF-23 (before infusion: 68 median [first to third quartile: 58–97] relative unit (RU)/mL, after infusion: 67 [57–77] RU/mL, P  = 0.37). DN patients were 65 ± 9 years old. During ACEi + RS treatment, eGFR was 65 ± 25 mL/min/1.73 m 2 and albuminuria 649 mg/d (230–2008 mg/d). FGF23 level was 94 (73–141) RU/mL during ACEi therapy. FGF-23 did not change significantly by add-on HCT (99 [74–148] RU/mL), LS diet (99 [75–135] RU/mL), or their combination (111 [81–160] RU/mL, P  = 0.15). Acute and chronic changes in volume status did not materially change FGF-23 in hypertensive patients and DN, respectively. Our data do not support a direct feedback loop between volume status and FGF-23 in hypertension or DN.